Analysis of inhibition action of acacia nilotica ethanol extract on aluminium corrosion in 1.0M HCl and NaOH - S.U, Abdul; M.B, Ibrahim; M. A., Ibrahim (International Journal of Advanced Chemistry, 2021)
The proposed corrosion inhibition action of Acacia nilotica ethanol extract on aluminium corrosion in HCl and NaOH was investigated using weight loss method. The Acacia nilotica ethanol extract was found to be inactive in NaOH at all the concentrations of the inhibitor but active in HCl with increasing inhibition efficiency as inhibitor concentration and decreases as temperature increases with the highest inhibition efficiency of 95.31%. The kinetic and thermodynamics data shows that the adsorption process was feasible and endothermic adsorption process from the large negative values of Gibbâ€™s free energy (Î”G) and negative values of enthalpy (Î”H), The data indicated physisorption process of adsorption which was supported by FTIR spectra. The adsorption process was best fitted to Langmuir adsorption model. Â Â